2015
DOI: 10.5027/andgeov42n1-a02
|View full text |Cite
|
Sign up to set email alerts
|

Estructura neógena de la Precordillera Andina, Argentina: aportes de modelos análogos.

Abstract: ABSTRACT. Analogue models combining different sets of preexisting structural weaknesses were developed to understand their evolution during regional ~ENE shortening. Strain analysis of simulations was performed with the GEODEF 1.1 software, a tool that allows to quantify deformation in plan view on the basis of displacement fields. Results showed up that regional NNE heterogeneities are reactivated as dextral reverse-slip structures, though NNE neoformed thrusts are also present. Likewise, dominant sinistral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…7b) suggest a probable 'inherited' nature of the highly oblique lineaments. Analogue modelling and gravimetric data considered by Oriolo (2012) and Oriolo et al (2012) have also supported this hypothesis. Likewise, analogue models from these authors have demonstrated that crossstrike structures do not develop unless they represent pre-existing crustal fabrics but they reactivate after the main shortening in orogenic along-strike structures has occurred.…”
Section: Temporal and Kinematic Evolution Of Cross-strike Structuressupporting
confidence: 55%
See 1 more Smart Citation
“…7b) suggest a probable 'inherited' nature of the highly oblique lineaments. Analogue modelling and gravimetric data considered by Oriolo (2012) and Oriolo et al (2012) have also supported this hypothesis. Likewise, analogue models from these authors have demonstrated that crossstrike structures do not develop unless they represent pre-existing crustal fabrics but they reactivate after the main shortening in orogenic along-strike structures has occurred.…”
Section: Temporal and Kinematic Evolution Of Cross-strike Structuressupporting
confidence: 55%
“…Cross-strike structures in the study area indicate the presence of the Hualila ´n Belt (Oriolo et al 2011;Oriolo 2012), which is equivalent to the Talacasto lineament previously defined by Re ét al. (2001) and which represents the structural control of the Miocene Central Volcanic Belt of the Precordillera (Oriolo 2012).…”
Section: Relationship Between Cross-strike Structures and Miocene Mag...mentioning
confidence: 53%